Leishmania manipulation of sand fly feeding behavior results in enhanced transmission. - Matthew E Rogers; Paul A Bates (PLoS Pathogens)
In nature the prevalence of Leishmania infection in whole sand fly populations can be very low (<0.1%), even in areas of endemicity and high transmission. It has long since been assumed that the protozoan parasite Leishmania can manipulate the feeding behavior of its sand fly vector, thus enhancing transmission efficiency, but neither the way in which it does so nor the mechanisms behind such manipulation have been described. A key feature of parasite development in the sand fly gut is the secretion of a gel-like plug composed of filamentous proteophosphoglycan. Using both experimental and natural parasite-sand fly combinations we show that secretion of this gel is accompanied by differentiation of mammal-infective transmission stages. Further, Leishmania infection specifically causes an increase in vector biting persistence on mice (re-feeding after interruption) and also promotes feeding on multiple hosts. Both of these aspects of vector behavior were found to be finely tuned to the differentiation of parasite transmission stages in the sand fly gut. By experimentally accelerating the development rate of the parasites, we showed that Leishmania can optimize its transmission by inducing increased biting persistence only when infective stages are present. This crucial adaptive manipulation resulted in enhanced infection of experimental hosts. Thus, we demonstrate that behavioral manipulation of the infected vector provides a selective advantage to the parasite by significantly increasing transmission.